2019
DOI: 10.1021/acs.jmedchem.9b00751
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Conformationally Restricted Human Glutaminyl Cyclase Inhibitors as Potent Anti-Alzheimer’s Agents by Structure-Based Design

Abstract: Alzheimer’s disease (AD) is an incurable, progressive neurodegenerative disease whose pathogenesis cannot be defined by one single element but consists of various factors; thus, there is a call for alternative approaches to tackle the multifaceted aspects of AD. Among the potential alternative targets, we aim to focus on glutaminyl cyclase (QC), which reduces the toxic pyroform of β-amyloid in the brains of AD patients. On the basis of a putative active conformation of the prototype inhibitor 1, a series of N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…When assayed in the 5XFAD mouse model, compound 136 effectively reduced the concentrations of pyroform Aβ in the brain after 4 weeks of i.p. administration …”
Section: Recent Design Of Urea Derivatives In Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…When assayed in the 5XFAD mouse model, compound 136 effectively reduced the concentrations of pyroform Aβ in the brain after 4 weeks of i.p. administration …”
Section: Recent Design Of Urea Derivatives In Drug Discoverymentioning
confidence: 99%
“…administration. 248 Disfunction of beta 2-adrenergic receptor (β 2 AR) has been recently related to AD and other neurodegenerative disorders, although the mechanisms involved are still poorly understood. Gaiser and co-workers recently developed bitopic urea-based ligands in order to target the orthosteric binding site (OBS) and a metastable binding site (MBS) on β 2 AR.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…SAR analyses indicated that these conformationally restrained compounds had improved QC inhibitory potency, and the Z - E conformation of the compound at the active site was critical for activity. For example, compound 90 (IC 50 = 6.1 nM, Figure ) showed promising efficacy and significantly reduced the brain concentrations of pE-Aβ and total Aβ in the 5XFAD mouse model …”
Section: Discovery and Development Of Qc Inhibitorsmentioning
confidence: 99%
“…For example, compound 90 (IC 50 = 6.1 nM, Figure 7) showed promising efficacy and significantly reduced the brain concentrations of pE-Aβ and total Aβ in the 5XFAD mouse model. 141 Related studies have pushed the discovery of yet other novel QC inhibitors. For instance, a small molecule, 1, was synthesized, which exhibited an IC 50 value of 5.11 μM (Figure 7).…”
Section: Discovery and Development Of Qcmentioning
confidence: 99%
“…Several inhibitors of the homologous human glutaminyl cyclase (hQC), derived from either imidazole benzimidazole or other zinc-binding groups, have been reported [28][29][30][31][32][33][34][35][36][37][38][39][40]. The examination of the inhibitory potency of imidazole, imidazole derivatives, and benzimidazole as zinc binding fragments against PgQC revealed different activities from those observed in the human enzyme (Figure 1).…”
Section: Inhibitor Designmentioning
confidence: 99%